Evaluation of Dietary Probiotic (Lactobacillus plantarum BG0001) Supplementation on the Growth Performance, Nutrient Digestibility, Blood Profile, Fecal Gas Emission, and Fecal Microbiota in Weaning Pigs - Huan Wang; In-Ho Kim (Animals, 2021)
A total of 180, 4-week-old crossbred weaning piglets ((Yorkshire × Landrace) × Duroc; 6.67 ± 1.40 kg) were used in a 42 day experiment to evaluate the effect of dietary probiotics (Lactobacillus plantarum BG0001) on growth performance, nutrient digestibility, blood profile, fecal microbiota, and noxious gas emission. All pigs were randomly allotted to one of four treatment diets in a completely randomized block design. Each treatment had nine replicates with five pigs/pen (mixed sex) Designated dietary treatments were as: (1) basal diet (NC), (2) NC + 0.2% antibiotics (chlortetracycline) (PC), (3) NC + 0.1% L. plantarum BG0001 (Lactobacillus plantarum BG0001) (NC1), (4) NC + 0.2% L. plantarum BG0001 (NC2). On d 42, BW and G:F were lower (p < 0.05) in pigs fed NC diet compared with PC diet and probiotic diets. Throughout this experiment, the average daily gain increased (p < 0.05) in pigs when fed with PC and probiotic diets than the NC diet. The average daily feed intake was higher (p < 0.05) in pigs fed PC diet during day 0–7 and 22–42, and probiotic diets during day 0–7 compared with NC diet, respectively. The Lactobacillus count was increased and Escherichia coli count was decreased (p < 0.05) in the fecal microbiota of pigs fed probiotic diets, and E. coli were decreased (p < 0.05) when fed a PC diet compared with the NC diet on day 21. Moreover, the apparent total tract nutrient digestibility, blood profile, and the concentration of noxious gas emission had no negative effects by the probiotic treatments. In conclusion, dietary supplementation with L. plantarum BG0001 significantly improved the growth performance, increased fecal Lactobacillus, and decreased E. coli counts in weaning pigs.